O ensino profissionalizante em Sergipe : contribuição do Instituto Profissional Coelho e Campos (1922-1944) - Malta, Marina Oliveira (2010)
The target of this study was to investigate the trajectory of Instituto Profissional Coelho e Campos , ordering to notice what the contribution of this Institution for the professional teaching in Sergipe. The period of the research was in 1922, date of creation of the Institute, until 1944, when this was subordinated to Serviço Nacional de Aprendizagem Industrial . This is a historic research, which is based on the assumptions of New Cultural History. The categories of analysis are the concepts of figuration and configuration and civilization of Norbert Elias; field, power, capital and habitus of Pierre Bourdieu, such as appropriation and representation of Roger Chartier. It was made a bibliographic research on the thematic of professional education, to notice the ways of this teaching throughout History of Education. The sources were located in Arquivo Público Estadual de Sergipe , in Biblioteca da Universidade Federal de Sergipe , in PESQUISE Pesquisas de Sergipe , in Biblioteca Pública Epiphâneo Dórea , in Arquivo do Poder Judiciário , in Instituto Histórico e Geográfico de Sergipe , in Centro de Documentação e Informações da Câmara dos Deputados and in Arquivo do Senado Federal . The propose of this study, is to contribute with the researches in the area of History of Education to make considerations about professional teaching and their practical training.